Burnout syndrome indices in Greek intensive care nursing personnel - Papathanassoglou, Elizabeth; Karanikola, Maria; Mpouzika, Meropi (My University, 2012)
Burnout symptoms in Greek intensive care unit (ICU) nurses have not been explored adequately. The aim of this descriptive, correlational study was to investigate the prevalence and intensity of burnout symptoms in Greek ICU nursing personnel and any potential associations with professional satisfaction, as well as with demographic, educational, and vocational characteristics. Findings showed that the overall burnout level reported by Greek ICU nursing personnel was at a moderate to high degree. The most pronounced symptom of burnout was depersonalization, whereas emotional exhaustion was found to be a strong predictor of job satisfaction. This is a factor connected with the nurses' intention to quit the job. It appears that work factors have a more powerful influence over the development of burnout in comparison to personality traits
Keywords: Critical care nursing; Intensive care nursing; Greece; Distress (Psychology); Intensive care units; Job satisfaction; Burnout (Psychology)